Risk Factors for Operative Treatment of Intussusception: A Single Centre Study in Low-and middle- income country Perspective - Chowdhury , Tanvir Kabir; Ayesha Sadia; Fatima Farhana Rini; Mohammad Zonaid Chowdhury; Shabeha Sultana; Adnan Walid; Md. Qumrul Ahsan (Asian Journal of Clinical Pediatrics and Neonatology, 2022)
Introduction: Although, non-operative treatment is a well-established method of treatment of intussusception, surgical intervention is still needed in some patients. Early recognition of these patients can reduce morbidity and mortality. The aim of the study was to find out the risk factors for surgery in these patients. Subjects and Methods: A retrospective analysis was performed among 225 patients of intussusception in a tertiary government teaching hospital between 2016 and 2019. Patients were evaluated for demographic features, presenting features with duration, examination findings, attempt for hydrostatic reduction, success and failure of hydrostatic reduction, type of surgery and mortality. Logistic regression analysis was performed to find out the risk factors. Results: Male to female ratio was 2.2:1, age ranged from 1.5 months to 8 years (median 8 months) and median weight was 8 kg. Duration of symptoms ranged from 1 to 14 days (mean 2.61 days). Hydrostatic reduction was attempted in 141 (62.7%) patients and was successful in 125 (88.7% ) patients. 100 (44.4%) patients underwent surgery. The risk factors for surgery were symptoms >48 hours (P<0.01), abdominal distension (P=0.01), per rectal bleeding (P=0.03), constipation (P<0.01), raised temperature (P=0.01), palpable abdominal mass (P=0.01) and presence of red currant jelly (P=0.04). Surgeries performed were manual reduction (65), intestinal resection anastomosis (18), intestinal stoma (13) and intestinal resection anastomosis with proximal stoma (4). There were 6 (2.7%) mortalities, all after surgery. Conclusion: The identified risk factors for surgery may help in the early and prompt referral of patients with intussusception.